Collaborative team dynamics and scholarly outcomes of multidisciplinary research teams: A mixed-methods approach. Issue 1 (3rd February 2023) - Slade, Emily; Kern, Philip A.; Kegebein, Robert L.; Liu, Chang; Thompson, Joel C.; Kelly, Thomas H.; King, Victoria L.; DiPaola, Robert S.; Surratt, Hilary L.
Abstract: Introduction: Impactful, transdisciplinary scientific discoveries are created by teams of researchers spanning multiple disciplines, but collaboration across disciplines can be challenging. We examined how team dynamics and collaboration are related to successes and barriers faced by teams of researchers from multiple disciplines. Methods: A mixed-methods approach was used to examine 12 research teams granted multidisciplinary pilot awards. Team members were surveyed to assess their team dynamics and individual views about transdisciplinary research. Forty-seven researchers (59.5%) responded, including two to eight members from each funded team. Associations were examined between collaborative dynamics and scholarly product outcomes, including manuscripts, grant proposals, and awarded grants. One member from each team was selected for an in-depth interview to contextualize and extend information about collaborative processes, successes, and barriers to performing transdisciplinary research. Results: Quality of team interactions was positively associated with achievement of scholarly products ( r = 0.64, p = 0.02). Satisfaction with team members ( r = 0.38) and team collaboration scores ( r = 0.43) also demonstrated positive associations with achievement of scholarly products, but these were not statistically significant. Qualitative results support these findings and add further insight into aspects of the collaborative process that were particularly important to foster success on multidisciplinary teams. Beyond scholarly metrics, additional successes from the multidisciplinary teams were identified through the qualitative portion of the study including career development and acceleration for early career researchers. Conclusions: Both the quantitative and qualitative study results indicate that effective collaboration is critical to multidisciplinary research team success. Development and/or promotion of team science-based trainings for researchers would promote these collaborative skills.